THE DESIGN OF FUEL DISTRIBUTION INFORMATION SYSTEM AT PT. RUDY AGUNG LAKSANA JAMBI - Hendri Hendri; Steven Chen; Fachruddin Fachruddin (International Conference on Business Management and Accounting, 2022)
PT. Rudy Agung Laksana Jambi is one of the companies engaged in the distribution of fuel oil which is located in the Jambi area where the fuel distribution system still uses Microsoft Excel. The enterprise have some problems due to the fact the inventory of oil ordered to Pertamina is limited, so orders from those clients delays from each the middle and company branches. Problems in data such as duplicate data, data storage that is still separate so that the difficulty in finding data, and making the result report is less effective and efficient to be presented to the owner of the company. Therefore, this paper aims to provide a solution to the problems that occur by offering FUEL distribution information systems using web programming with PHP language and MySQL database where the author develops the system with the new system produces output that can display customer data, supplier data, product data, purchase data, and income data, and can print reports needed to be presented to the owner of the company.